Public Frame Building: The Role of Source Usage in Times of Crisis - van der Meer, Toni G. L. A. (Communication research, 2018)
New media have markedly enhanced the public’s capacity to influence the framing of an issue, especially within crisis situations. By relying on research triangulation, this study aims to map the comprehensive frame-building process of the public as an understudied domain within framing and crisis research. Study 1 uses advanced automated content analyses of crisis-related tweets (N = 252,711) to examine how the public built frames online with the use of information sources. Study 2 applies an innovative vignette study (N = 772) to investigate the conditions that influence the public’s source selection during crises. The findings illustrate how the public uses sources to address certain frame functions and show that source usage is subject to external factors (i.e., crisis origin and magnitude) as well as internal factors (i.e., crisis involvement and habitual source use).